Using social media to engage students in campus life - Ternes, Jacob A. (Kansas State University, 2013)
Social media is the use of online applications and websites to create and exchange user-generated content. These websites are becoming ever more popular with college aged students to connect with their peers, businesses, and areas of interest. These websites could be taken advantage of to provide new opportunities to engage students in campus life. This paper examines the concept of student engagement and the role of social media in engaging student with campus life. A brief overview of Facebook and Twitter, the two most popular social networks, is provided. This paper also reviews the limited body of research available on the impact of social media on student engagement. It is argued here that social media can be a positive influence on student engagement within the college campus and could lead to improvements in the way that higher education professional assist with student development. Due to the limited amount of academic research available, popular news sources as well as websites and blogs were examined to determine the most influential uses of social media, and this report makes recommendations for incorporating social media use into higher education. Social media allows higher education professionals to “meet students where they are” and provide for opportunities for engagement and student development. If the recommendations made in this report are implemented by student affairs professionals, they could be assessed for their impact on student engagement and development in the future.
Keywords: Social media; Facebook; Twitter; Engagement; Higher Education (0745)